THE URGENCY OF LEGAL REGULATIONS RELATING TO THE AUTHENTICATION OF EVIDENCE ELECTRONICS IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Fayadh Ayyasi Regar; Milda Istiqomah; Faizin Sulistio (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the urgency of electronic evidence authentication in the Indonesian criminal justice system and formulate future legal regulations that provide legal certainty regarding the validity of electronic evidence. The research method used is a juridical-normative with a statutory and conceptual approach, which is based on a literature review of national regulations and international legal instruments such as the Budapest Convention. The results of the study indicate that the absence of provisions for electronic evidence authentication in the Criminal Procedure Code creates legal uncertainty and opens up opportunities for digital evidence manipulation in court. The discussion emphasizes the importance of digital forensics as a technical authentication mechanism to ensure the integrity, authenticity, and reliability of electronic evidence. In addition, the conformity of electronic evidence with the principles of relevance and legality is still not fully regulated in the criminal procedural law system. The conclusion of this study is that electronic evidence authentication needs to be immediately regulated firmly in legislation as a form of adaptation to developments in information technology to realize justice and legal certainty in the digital era